Effect of N2 on Biological Methanation in a Continuous Stirred-Tank Reactor with Methanothermobacter marburgensis - Marc Philippe Hoffarth (Fermentation, 2019)
In this contribution, the effect of the presence of a presumed inert gas like <semantics> N 2 </semantics> in the feed gas on the biological methanation of hydrogen and carbon dioxide with Methanothermobacter marburgensis was investigated. <semantics> N 2 </semantics> can be found as a component besides <semantics> CO 2 </semantics> in possible feed gases like mine gas, weak gas, or steel mill gas. To determine whether there is an effect on the biological methanation of <semantics> CO 2 </semantics> and <semantics> H 2 </semantics> from renewable sources or not, the process was investigated using feed gases containing <semantics> CO 2 </semantics> , <semantics> H 2 </semantics> , and <semantics> N 2 </semantics> in different ratios, depending on the <semantics> CO 2 </semantics> content. A possible effect can be a lowered conversion rate of <semantics> CO 2 </semantics> and <semantics> H 2 </semantics> to <semantics> CH 4 </semantics> . Feed gases containing up to 47% <semantics> N 2 </semantics> were investigated. The conversion of hydrogen and carbon dioxide was possible with a conversion rate of up to 91% but was limited by the amount of <semantics> H 2 </semantics> when feeding a stoichiometric ratio of 4:1 and not by adding <semantics> N 2 </semantics> to the feed gas.